Asymptotic normality of conditional density and conditional mode in the functional single index model - Akkal, Fatima; Kadiri, Nadia; Rahbi, Abbes (Asymptotyczna normalność rozkładu warunkowej gęstości i warunkowej dominanty modelu jednowskaźnikowego, 2021)
The main objective of this paper is to investigate the nonparametric estimation of the conditional density of a scalar response variable Y, given the explanatory variable X taking value in a Hilbert space when the sample of observations is considered as an independent random variables with identical distribution (i.i.d) and are linked with a single functional index structure. First of all, a kernel type estimator for the conditional density function (cond-df) is introduced. Afterwards, the asymptotic properties are stated for a conditional density estimator when the observations are linked with a singleindex structure from which one derives a central limit theorem (CLT) of the conditional density estimator to show the asymptotic normality of the kernel estimate of this model. As an application the conditional mode in functional single-index model is presented, and the asymptotic (1 – ζ) confidence interval of the conditional mode function is given for 0 < ζ < 1. A simulation study is also presented to illustrate the validity and finite sample performance of the considered estimator. Finally, the estimation of the functional index via the pseudo-maximum likelihood method is discussed
Econometrics = Ekonometria, 2021, Vol. 25, No. 1, s. 1-24
Keywords: asymptotic normality; conditional density; functional single index model; functional random variable; nonparametric estimation; asymptotyczna normalność; gęstość warunkowa; funkcjonalny model pojedynczego wskaźnika; funkcjonalna zmienna losowa; estymacja nieparametryczna